Tracking control with event‐triggered strategy for multi‐agent systems with noises. (31st May 2018) - Tang, Zhaojun; Li, Chuandong
Summary: This paper is concerned with a tracking control problem of multi‐agent systems with noises. It is assumed that each agent in the network updates its state only at some discrete time instants, which determined by the event‐triggered condition, and the agents are affected by noises. In order to attenuate the effect of noises, consensus‐gain function is introduced in the control protocol. Centralized and decentralized event‐triggered protocols are proposed to ensure that the followers track the considered leader. With the help of matrix theory and Lyapunov method, sufficient conditions are derived to solve the mean square tracking control. Simulation results are provided to illustrate the theoretical results.